Significance of the Study on Regional Dialects in Assamese Language - Borah, Jahnabi; Sharma, Ujjal (International Journal of Computer Sciences and Engineering, 2015)
In any natural language there are two linguistic variations: dialect and accent. In any standard natural language, the presence of various dialects can be seen due to the pattern of pronunciation and the vocabularies used by a particular community because of geographical differences. Assamese Language also has several dialect variations based on the phonology and morphology. Recent studies show that there are four dialect groups in this language. Since very little work has been done in the regional dialect of Assamese language, it has become necessary to discriminate these dialects as it seems no significant and systematic study is carried out on the dialects of Assamese language. In this paper a study has been done to show the works that have been done in the area of Automatic dialect classification/recognition of some Foreign and Indian languages till date. Also the phonology and morphology of Assamese language and the need to study the dialects present in the language has been discussed.